Dermatology - Bolognia, Jean; Jorizzo, Joseph L.; Schaffer, Julie V. (Elsevier Saunders, 2012)
A title that puts various practices in dermatologic diagnosis and treatment at your fingertips. It a comprehensive coverage of basic science, clinical practice, pediatric dermatology, and dermatologic surgery. Whether you're a resident or an experienced practitioner, it offers answers you need to overcome any challenge you face in practice.